Climate-induced heat stress incorporated in Ugandan government strategies supported by the Prime Minister Delivery Unit (PMDU) - CGIAR Research Program on Livestock (2020)
The PMDU has expressed the intention to support the incorporation of heat stress issues into government policies and strategies and implementation